The infinity particle - Xu, Wendy (2023)
"Clementine Chang moves from Earth to Mars for a new start and is lucky enough to land her dream job with Dr. Marcella Lin, an Artificial Intelligence pioneer. On her first day of work, Clem meets Dr. Lin's assistant, a humanoid AI named Kye. Clem is no stranger to robots--she built herself a cute moth-shaped companion named SENA. Still, there's something about Kye that feels almost too human. When Clem and Kye begin to collaborate, their chemistry sets off sparks. The only downside? Dr. Lin is enraged by Kye's growing independence and won't allow him more freedom. Plus, their relationship throws into question everything Clem thought she knew about AI. After all, if Kye is sentient enough to have feelings, shouldn't he be able to control his own actions? Where is the line between AI and human? As her past and Kye's future weigh down on her, Clem becomes determined to help him break free--even if it means risking everything she came to Mars for"--
Keywords: Robots -- Comic books, strips, etc; Artificial intelligence -- Comic books, strips, etc; Human-robot interaction -- Comic books, strips, etc; Space colonies -- Comic books, strips, etc; Love -- Comic books, strips, etc; Graphic novels; Mars (Planet) -- Comic books, strips, etc; Science fiction comics; Graphic novels